The Formulation of High-Calorie and Rich-Fe Biscuits for Pregnant Women with Chronic Energy Malnutrition - Sunarti Sunarti; Diffah Hanim; Mustofa Ahda; Ahid Mudayana; Kusnandar Kusnandar (Intelektual Pustaka Media Utama, 2016)
Supplementary food distribution for pregnant women still depends on the local policy. This program is funded using Health Operational Funds and distributed in form of milk, eggs, raw materials such as green beans and others. The field constraints of this program were acceptability and willingness of pregnant women to process the raw materials. This study aims to address the problems of providing supplementary food for pregnant women who suffer from chronic energy malnutrition and anemia by making the formulation of high protein biscuits and Fe using soybean flour substitution catfish eggs and flour as a source of protein and Fe. Biscuits produced is expected to be one of the snacks and nutritions for women who suffer from chronic energy deficeincy. The ingredients were flour, fish powder, soy flour, eggs, milk powder, sugar, and maize flour. The method used was pure experimental approach completely randomized design with three times repetition. The formulation of the biscuits proportion between fish and soy flour as much as 2:1, 1:1, and 1:2. Proximate test shows that the proportion of fish and soy flour 1:2 has the highest energy value (496.81 kcal) with a value of 17.74% protein. Organoleptic test indicates that the most favorable taste and tekstur was the formulation with the proportion of fish flour and soy flour 1:2. The formulation of high protein and Fe biscuits for women with chronic energy malnutrition and anemia in Boyolali favoured by third trisemester pregnant women is the one with the proportion of 1:2.